#### Answer

b = -2

#### Work Step by Step

2b + 4 = -18 - 9b
First, you need to get the variable (b) on one side of the equation, so add 9b to both sides of the equation. This will remove the b from the right side of the equation.
2b + 4 + 9b = -18 - 9b + 9b
Simplify to get this:
11b + 4 = -18
Subtract 4 from each side.
11b + 4 - 4 = -18 - 4
Simplify to get:
11b = -22
Divide each side by 11.
$\frac{11b}{11}$ = $\frac{-22}{11}$
Simplify to b = -2
We check our answer to find that our answer is, indeed, correct.